2011
DOI: 10.1097/prs.0b013e3182043a07
|View full text |Cite
|
Sign up to set email alerts
|

Role of Indian Hedgehog Signaling in Palatal Osteogenesis

Abstract: Introduction Cleft lip and palate are common birth defects and represent a large biomedical burden. Through the use of animal models, the molecular underpinnings of cleft palate are becoming increasingly clear. Indian Hedgheg (Ihh) has been shown to be associated craniofacial development and active in the palatine bone. We hypothesize that Ihh activity plays a role in osteogenesis within the secondary palate and that defects in this pathway may inhibit the osteogenesis of the secondary palate. Methods Palate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…It has been proven that differentiation induced by 10 −8 mol/L DEX induces osteogenesis in MSCs [15]. Our study confirmed that DEX promoted osteoblast differentiation in rat mesenchymal stem cells at the concentration of 10 −8 mol/L from seven days to 21 days, demonstrated by up-regulation ALP activity and expression of osteoblast-associated markers type I collagen.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It has been proven that differentiation induced by 10 −8 mol/L DEX induces osteogenesis in MSCs [15]. Our study confirmed that DEX promoted osteoblast differentiation in rat mesenchymal stem cells at the concentration of 10 −8 mol/L from seven days to 21 days, demonstrated by up-regulation ALP activity and expression of osteoblast-associated markers type I collagen.…”
Section: Discussionsupporting
confidence: 76%
“…After pre-culture for 24 hours, the MSCs were allowed to culture in osteogenesis culture medium (including 10 −8 mol/L Dexamethasone, 10 mmol/L β-glycerophosphate, 50 μg/ml ascorbic acid and 50 μg/ml vitamin C) according to the experimental requirements for up to 21 days [15]. All MSCs were incubated in 5 % CO2 at 37°C, and the medium was replaced every three days before harvest.…”
Section: Induction Of Osteoblast Differentiation In Rat Mscsmentioning
confidence: 99%
“…In addition, effects of various protein ligands on palatal gene expression can be studied. 48,49 The disadvantage, of course, is that in vitro conditions do not completely mimic in vivo correlates, and thus palate cultures are better for analyzing pathways than morphogenesis.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…90 For example, at E16.5 and E17.0, an appreciable decrease in size of palatine bones was observed in the Ihhj/j mice as compared with Ihh+/+ littermates, which caused a cleft in the midline of the palatine bone. 91 Shh is the most broadly expressed member of the hedgehog signaling, and is expressed in the palatal mesenchyme and epithelium. 92 Previous studies have shown that Shh inhibition results in a cleft palate, 92 and abrogation of Shh function in the palatal epithelium generates cleft palate.…”
Section: Hedgehog Signalingmentioning
confidence: 99%